KARAKTERISTIK GELOMBANG DAN ARUS DI ERETAN, INDRAMAYU - Hadikusumah, Hadikusumah (UI Scholars Hub, 2009)
The Wave and Current Characteristic at Eretan, Indramayu. Erosion process occurs in many places, but each of these processes have their respective characteristics. The purpose of research for understanding the dynamics of the process that caused the coastline of the interaction between air, sea and land. Research has been conducted in Eretan, Indramayu in 2006. The results show the average wave height (H1/3) in February obtained higher (60.4 cm) compared with August (23.6 cm) and in May obtained a much lower (5.7 cm). Current velocity in February and in August obtained dominant raised due to by field of wave and the influence of tidal currents do not exist. Instead current velocity obtained in May was raised by the dominant tidal currents and very small currents generated by the wave field. The influence of the wave field to the velocity and direction of flow will distribute sediment transport in the area of wave breack (breack water) to the coastline. Characteristic wave has a period of 3, 5, and 7 second is the trigger shoreline retreat 1.5 m/year.